Developing a definition of biofortification through the synthesis of food biofortification publications: A scoping review protocol - Kellogg, Julianne A.; Klarquist, Emily F.; Waziri, Aichatou D.; Luftig, David; Carbonero, Franck; Aytekin, Destan; Walton, Jenny (JBI, 2022)
Objective: The objective of this review is to develop a definition of biofortification through the synthesis of food biofortification publications and to document the breadth of the research on this topic. Introduction: Biofortification of a food source is a human health intervention. Due to the varying definitions of this concept, biofortification can be difficult to describe. Originally, biofortification was defined as the use of plant breeding methods to produce staple foods, dense in minerals and vitamins. Research using the term focused on mineral, vitamin, and protein improvement of staple foods. However, the field has expanded to include non-staple foods as well as different methodological approaches to biofortification (eg, transgenic, molecular breeding). Researchers require a broad overview of the evidence and consensus on a definition to ensure effective communication within this scientific community. Inclusion criteria: Inclusion criteria will be broad to ensure that existing definitions of biofortification are captured across the different areas of study in this field. The review will consider research published in English. Inclusion will not be limited by participant type, date of publication, or context. The concept will be strictly biofortification. Methods: A broad search strategy will be utilized for AGRICOLA, AGRIS, Web of Science, PubAg, CINAHL, PubMed, Cochrane Library, Epistemonikos, JBI Evidence Synthesis, Google Scholar, and Washington State University Libraries’ integrated catalog. A limited search for gray literature will be conducted. The data extracted will include study and author characteristics. Tables and figures will demonstrate the breadth of the evidence.